Atomic‐Level Sculpting of Crystalline Oxides: Toward Bulk Nanofabrication with Single Atomic Plane Precision. Issue 44 (19th October 2015) - Jesse, Stephen; He, Qian; Lupini, Andrew R.; Leonard, Donovan N.; Oxley, Mark P.; Ovchinnikov, Oleg; Unocic, Raymond R.; Tselev, Alexander; Fuentes‐Cabrera, Miguel; Sumpter, Bobby G.; Pennycook, Stephen J.; Kalinin, Sergei V.; et al.
Abstract : The atomic‐level sculpting of 3D crystalline oxide nanostructures from metastable amorphous films in a scanning transmission electron microscope (STEM) is demonstrated. Strontium titanate nanostructures grow epitaxially from the crystalline substrate following the beam path. This method can be used for fabricating crystalline structures as small as 1–2 nm and the process can be observed in situ with atomic resolution. The fabrication of arbitrary shape structures via control of the position and scan speed of the electron beam is further demonstrated. Combined with broad availability of the atomic resolved electron microscopy platforms, these observations suggest the feasibility of large scale implementation of bulk atomic‐level fabrication as a new enabling tool of nanoscience and technology, providing a bottom‐up, atomic‐level complement to 3D printing. Abstract : An aberration‐corrected e‐beam in a scanning transmission electron microscope can be used to crystallize amorphous complex oxides with atomic plane precision. Using this control system, epitaxial growth of SrTiO3 is achieved to pattern text onto a 90 × 25 nm area.